Students’ strategies in learning writing online: A case at English Education Department - Hapsari , Mustika Dwiki Herning; Nur Fatimah; Nguyen, Tran Thi Hoang (Universitas Ahmad Dahlan, 2024)
Writing is one of the fundamental language skills. To address the need for effective writing strategies, this study aims to describe students' learning strategies for developing writing skills when learning writing online. This research employs a mixed-method approach. Data collection techniques include a questionnaire and interview. The Inventory of Learning Strategies, based on and modified from Oxford (1990), was validated and used for this study. The questionnaire was distributed to 190 sixth-semester students in the English Education Department. The questionnaire data was analyzed using Microsoft Excel to determine the frequency of each strategy. Additionally, interviews were conducted with 12 students from the same department, and the results were classified according to Oxford's learning strategy classifications. The research findings indicate that students in the English Education Department utilize all learning strategies: metacognitive, memory, cognitive, compensation, affective, and social strategies. Compensation strategies were the most frequently used (19.46%). It is followed by metacognitive strategies (16.67%), affective strategies (16.65%), social strategies (15.36%) and memory strategies (14.95%) in learning writing online. This can facilitate teachers to find out the suitable teaching methods that accommodate the strategies used by students so that they can learn the language especially in writing more easily and more effectively.